ANTIBACTERIAL ACTIVITY OF Chaetoceros calcitrans AGAINST PATHOGEN Staphylococcus aureus AND Staphylococcus epidermidis CAUSING SKIN INFECTION - Patricia Gita Naully (BRIN - Badan Riset dan Inovasi Nasional, 2022)
The microalgae Chaetoceros calcitrans has potential as a natural antibacterial but is rarely applied to pathogens that cause skin infections such as Staphylococcus aureus and S. epidermidis. The purpose of this study was to determine the optimum concentration of C. calcitrans extract to inhibit the growth of S. aureus and S. epidermidis. The antibacterial activity of C. calcitrans was tested by the Kirby Bauer diffusion method. The results showed that C. calcitrans extract dissolved in DMSO with the concentrations of 5, 10, 15, and 25 mg mL-1 could produce inhibition zones on S. aureus and S. epidermidis. The average diameter of the largest inhibition zone resulted in the concentration of 25 mg mL-1, namely 10.1 ± 0.5 mm in S. aureus and 9.3 ± 0.5 mm in S. epidermidis. It can be concluded that the extract of C. calcitrans has antibacterial activity against bacteria that cause skin infections S. aureus and S. epidermidis with the optimum concentration of 25 mg mL-1.